Early childhood social and emotional development: Advancing the field of measurement - Darling-Churchill, Kristen E.; Lippman, Laura (Journal of applied developmental psychology, 2016)
This paper frames the subject of this special issue — how the field currently measures social and emotional development in early childhood. We first describe the relationship of social and emotional development to child functioning and overall well-being, and then present major measurement challenges associated with this domain, including a lack of clarity around conceptualizations of the subdomains of social and emotional development, and issues tied to quality and ease of use for extant measures. In describing the multiple purposes of early childhood assessment more broadly, the reciprocal dynamic between programs, policymakers, researchers, and developers in generating knowledge, guidance for practitioners, and policy is highlighted. We close with an overview of the remaining articles in this issue, and underscore the need for the field to come to agreement on sound conceptual and methodological approaches to measuring young children's social and emotional development. •Discusses current approaches to measuring social and emotional development in early childhood•Presents major measurement challenges associated with this domain•Describes multiple purposes of early childhood assessment more broadly•Discusses dynamic between programs, policymakers, researchers, and developers•Calls for the field to strive for conceptual and methodological agreement